A resilience evaluation method for a combined regional agricultural water and soil resource system based on Weighted Mahalanobis distance and a Gray-TOPSIS model. (20th August 2019) - Liu, Dong; Qi, Xiaochen; QiangFu; Li, Mo; Zhu, Weifeng; Zhang, Liangliang; Abrar Faiz, Muhammad; Khan, Muhammad Imran; Li, Tianxiao; Cui, Song
Abstract: Continuous urbanization, development of the economy, and the unrestrained exploitation and use of natural resources, the earth's ecosystems have been severely damaged by various types of frequently occurring natural and man-made disasters. Agricultural water and soil resources as a basic national strategic resources, a conflict is increasingly prominent between the available supply of and the increasing demand for these resources. Under such circumstances, the need for a quantitative diagnosis of the resilience of these types of has drawn increasing attention in China and abroad. A Technique for the Order of Preference by Similarity to an Ideal Solution (TOPSIS) evaluation model based on weighted Mahalanobis distance and gray relational analysis (MTS-GRA-TOPSIS) was proposed to evaluate the resilience of a combined regional agricultural water and soil resource (CRAWSR) system. For this purpose, a case study of the Jiansanjiang Administration of Agricultural Reclamation in Heilongjiang Province, China, was conducted. A total of 15 farms under its administration were used as evaluation objects, using information substitutability to screen out 12 indicators used to evaluate resilience. A MTS-GRA-TOPSIS model was used to evaluate the resilience rating of a CRAWSR system for 15 farms. The results show that the current resilience level of Jiansanjiang was rather low and that it should be improved. Specific countermeasures and suggestions were proposed, including increasing the utilization ratio of water and soil resources, returning farmland to forests, reducing groundwater use for agricultural irrigation, balancing the development of various industries, and improving the level of agricultural water conservation and mechanization. Verification of the rationality and reliability of the evaluation results obtained by the MTS-GRA-TOPSIS model was conducted which may be valuable for the formulation of related resource development strategies. Graphical abstract: Image 1 Highlights: Fifteen farms in Jiansanjiang, Heilongjiang Province, China, were chosen to produce model resilience matrices Weighted Mahalanobis distance and gray correlation analysis were used to improve the traditional TOPSIS evaluation model The information alternative method screened out 12 indicators for resilience evaluation Resilience of farms was rated at I, II, and III based on distribution and causes of resilience Degree of discrimination theory was used to analyze the reliability of model results